Suzana Marjanić and Antonija Zaradija Kiš, eds. Književna životinja. Kulturni bestijarij II. dio - Đurić, Ljubica (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Književna životinja. Kulturni bestijarij II. dio [The Literary Animal. A Cultural Bestiary. Part 2]. Ed. by Suzana Marjanić and Antonija Zaradija Kiš. Zagreb: Croatian University Press and Institute of Ethnology and Folklore Research, 2012, pp. 1144.